2016
DOI: 10.1590/1806-9282.62.05.414
|View full text |Cite
|
Sign up to set email alerts
|

Growth curves in Down syndrome with congenital heart disease

Abstract: Introduction: To assess dietary habits, nutritional status and food frequency in children and adolescents with Down syndrome (DS) and congenital heart disease (CHD). Additionally, we attempted to compare body mass index (BMI) classifications according to the World Health Organization (WHO) curves and curves developed for individuals with DS. Method: Cross-sectional study including individuals with DS and CHD treated at a referral center for cardiology, aged 2 to 18 years. Weight, height, BMI, total energy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…9 2.4 | Risk factors associated with development of T21 and CHD There are discrepancies regarding gender and the risk of CHD in patients with T21, CHD being more frequently reported in females. 1,5,6,11 Other studies have suggested male predominance. 12 Prenatal factors associated with T21-CHD include maternal smoking (adjusted relative risk 1.57 [1.18-2.09]) and obesity (BMI > 30 kg/m 2 ) with a 16%-34% increased risk.…”
Section: Neurodevelopmental Outcome In Patients With Chd and T21mentioning
confidence: 95%
See 2 more Smart Citations
“…9 2.4 | Risk factors associated with development of T21 and CHD There are discrepancies regarding gender and the risk of CHD in patients with T21, CHD being more frequently reported in females. 1,5,6,11 Other studies have suggested male predominance. 12 Prenatal factors associated with T21-CHD include maternal smoking (adjusted relative risk 1.57 [1.18-2.09]) and obesity (BMI > 30 kg/m 2 ) with a 16%-34% increased risk.…”
Section: Neurodevelopmental Outcome In Patients With Chd and T21mentioning
confidence: 95%
“…There are discrepancies regarding gender and the risk of CHD in patients with T21, CHD being more frequently reported in females . Other studies have suggested male predominance .…”
Section: Trisomy 21mentioning
confidence: 98%
See 1 more Smart Citation
“…Plotting a person on such DS specific curve only provide information about weight status compared to peers with DS and can classify a person with DS to be normal weight, that otherwise, by use of standard curves, would classify as overweight or obese (47). However, due to the shorter stature of individuals with DS, the curves and cut-offs developed for typical children have been found to overestimate obesity and percent body fat as measured by dualenergy X-ray absorptiometry (DXA) (48).…”
Section: Nutritional Statusmentioning
confidence: 99%
“…In adolescence and adulthood, patients with DS have a higher prevalence of overweight and obesity. Malnutrition followed by overweight and obesity may enhance risk to cardiovascular health compared to maintaining the same nutrition status over a period of time [130]. Use of DS specific growth charts are important for nutrition screening to accurately assess for both undernutrition and overweight/obesity and therefore to design a more targeted intervention [125].…”
Section: Nutrition Considerationsmentioning
confidence: 99%